Primary Tumors of the Spine - Orguc, Sebnem; Arkun, Remide (Seminars in Musculoskeletal Radiology, 2014)
Spinal tumors consist of a large spectrum of various histologic entities. Multiple spinal lesions frequently represent known metastatic disease or lymphoproliferative disease. In solitary lesions primary neoplasms of the spine should be considered. Primary spinal tumors may arise from the spinal cord, the surrounding leptomeninges, or the extradural soft tissues and bony structures. A wide variety of benign neoplasms can involve the spine including enostosis, osteoid osteoma, osteoblastoma, aneurysmal bone cyst, giant cell tumor, and osteochondroma. Common malignant primary neoplasms are chordoma, chondrosarcoma, Ewing sarcoma or primitive neuroectodermal tumor, and osteosarcoma. Although plain radiographs may be useful to characterize some spinal lesions, magnetic resonance imaging is indispensable to determine the extension and the relationship with the spinal canal and nerve roots, and thus determine the plan of management. In this article we review the characteristic imaging features of extradural spinal lesions.
Keywords: spinal tumor; extradural tumor; magnetic resonance imaging